2017
DOI: 10.1177/1074248417693379
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of LCZ696 in Patients With Hypertension Compared With Angiotensin Receptor Blockers

Abstract: LCZ696, a first-in-class angiotensin receptor neprilysin inhibitor, has been demonstrated to have greater advantages in the treatment of heart failure compared with angiotensin-converting enzyme inhibitors, enalapril, or angiotensin receptor blockers (ARBs). However, studies that compared the efficacy and safety of LCZ696 against valsartan in patients with hypertension are limited. To provide further evidence for the benefits of LCZ696 and to make this assessment, a meta-analysis of randomized controlled trial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
21
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 24 publications
4
21
0
4
Order By: Relevance
“…In our meta-analysis, we found that LCZ696 (100, 200, and 400 mg) produced significantly greater reductions in SBP, DBP, 24 h ASBP, and 24 h ADBP than ARBs alone in hypertensive patients. These results are consistent with the meta-analyses of Ye et al [21] and Zhao et al [23]. Compared with ARBs alone, LCZ696 causes a greater reduction in blood pressure, mainly attributed to RAS inhibition occurring simultaneously with neprilysin inhibition.…”
Section: Effects Of Lcz696 On Blood Pressure 597supporting
confidence: 91%
“…In our meta-analysis, we found that LCZ696 (100, 200, and 400 mg) produced significantly greater reductions in SBP, DBP, 24 h ASBP, and 24 h ADBP than ARBs alone in hypertensive patients. These results are consistent with the meta-analyses of Ye et al [21] and Zhao et al [23]. Compared with ARBs alone, LCZ696 causes a greater reduction in blood pressure, mainly attributed to RAS inhibition occurring simultaneously with neprilysin inhibition.…”
Section: Effects Of Lcz696 On Blood Pressure 597supporting
confidence: 91%
“…The BP-lowering effect was consistently observed across different clinical studies and was found to be dose-dependent and largely independent of age and baseline BP values, which ranged within stage 1–2 hypertension. These results confirmed and extended those of previous analyses, which showed similar beneficial effects on BP reduction [11].…”
supporting
confidence: 92%
“…In the study by Zhao et al[ 37 ], two drugs, including valsartan and olmesartan were used in ARB group, and the dose of olmesartan varied at 80mg, 160mg and 320mg in NCT00549770. The category and dose of drugs is likely to affect the effectiveness of reducing blood pressure.…”
Section: Discussionmentioning
confidence: 99%